The Effect of Mystery Box Media on Fourth Grade Students’ Interest in Science Learning - Syaira, Siti; Meilana, Septi Fitri (FKIP - Universitas Riau, 2025)
This study investigates the effect of Mystery Box media on fourth-grade students’ interest in learning Natural and Social Sciences (IPAS). The research was motivated by low student engagement due to monotonous teaching methods, limited variation in instructional media, and minimal opportunities for active participation, which reduce students’ enthusiasm during lessons. A quantitative approach using a quasi-experimental post-test only control group design was employed, involving two classes: the experimental class taught using Mystery Box media and the control class taught using conventional methods. A validated and reliable learning interest questionnaire served as the research instrument. Data analysis revealed that Mystery Box media significantly improved students’ learning interest, supported by a significance value (2-tailed) below 0.05 and an effect size of 2.073, categorized as very large. The findings indicate that Mystery Box media offers an engaging and interactive learning experience, encouraging higher student participation and enthusiasm, particularly in IPAS. This strategy is recommended as an innovative alternative to enhance students’ affective involvement in the learning process.